efektivitas metode Mubasyarah terhadap kemahiran berbahasa Arab siswa kelas tujuh di Sekolah Menengah Harsalakum Bengkulu. - M. Icsan Waly Yafei; Nukman Nukman; Akhirudin Akhirudin (El-Syaker : Samarinda International Journal of Language Studies, 2024)
The objective of this study is to assess the effectiveness of the Mubasyarah method in enhancing the Arabic language proficiency among seventh-grade students at Harsalakum Bengkulu Secondary School. The research employs a quasi-experimental quantitative approach. The target population consists of seventh-grade students at Harsalkam Bengkulu Secondary School, with cluster sampling used to select two groups: Class V-A (25 students) as the experimental group and Class VC-C (26 students) as the control group. Data collection involves pretest, treatment, and posttest phases. Analysis techniques include normality tests, homogeneity tests, and t-tests. Data analysis is conducted using SPSS version 26, and the t-test results show a significance value of  0.000, which is less than the threshold of 0.05 (0.000 < 0.05). Thus, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. Consequently, it can be concluded that the Mubasyarah method effectively enhances the language fluency of seventh-grade students at Harsalakum Bengkulu Secondary School.